2020
DOI: 10.1002/fsn3.1972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dietary approach to stop hypertension (DASH) diet on blood pressure, blood glucose, and lipid profile in adolescents with hemophilia: A randomized clinical trial

Abstract: Children with hemophilia are an enhanced risk of modifiable cardiovascular and metabolic abnormalities. There is currently no nutritional guideline to prevent or manage cardiometabolic risk factors in these patients. Therefore, the present study sought to investigate the effect of the Dietary Approaches to Stop Hypertension (DASH) diet on cardiovascular and metabolic risk factors among children with hemophilia. In this parallel randomized clinical trial, 40 children (all male) with hemophilia were randomly all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Saneei et al demonstrated that DASH diet could prevent the rise in diastolic BP (DBP) but not in systolic BP (SBP); also, no significant changes in glucose and lipid profiles were evident [ 80 ]. Mahdavi et al analyzed the effect of DASH Diet in a group of adolescents with hemophilia, which is an important CVD risk factor [ 91 ]. In the intervention group, they found lower SBP, but no effect on DBP; fasting glucose level was improved in the intervention group as well [ 91 ].…”
Section: Dash Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Saneei et al demonstrated that DASH diet could prevent the rise in diastolic BP (DBP) but not in systolic BP (SBP); also, no significant changes in glucose and lipid profiles were evident [ 80 ]. Mahdavi et al analyzed the effect of DASH Diet in a group of adolescents with hemophilia, which is an important CVD risk factor [ 91 ]. In the intervention group, they found lower SBP, but no effect on DBP; fasting glucose level was improved in the intervention group as well [ 91 ].…”
Section: Dash Dietmentioning
confidence: 99%
“…Mahdavi et al analyzed the effect of DASH Diet in a group of adolescents with hemophilia, which is an important CVD risk factor [ 91 ]. In the intervention group, they found lower SBP, but no effect on DBP; fasting glucose level was improved in the intervention group as well [ 91 ]. These different results may be explained by the different adherence to the dietary interventions (lower in the first study, higher in the second one) and the duration of the trials (6 weeks in first study, 10 weeks in the second one).…”
Section: Dash Dietmentioning
confidence: 99%
“…19 For youth with hemophilia, higher adherence to the DASH diet had beneficial effects on blood pressure and lipid profiles. 20 Adolescents with elevated blood pressure and hypertension also showed effective improvements in initial systolic blood pressure, longerterm endothelial function, and diet quality when following the DASH diet instead of routine care. 21 Additionally, the DASH diet was protective against gastroesophageal reflux disease.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, the Dietary Approaches to Stop Hypertension (DASH) diet, originally developed for the management of high blood pressure, has been proposed to potentially lower the levels of blood glucose (13).The DASH diet, a well-established healthy dietary pattern, underscores high consumption of fruits, vegetables, whole grains, nuts and legumes, moderate consumption of low-fat dairy products, as well as low consumption of sodium,sweetened beverages and red and processed meats (14). At the same time, DASH diet has been shown as one of three healthy diets recommended in the 2020-2025 United States Dietary Guidelines for the public (15).…”
Section: Introductionmentioning
confidence: 99%